ANALISIS KESULITAN PEMBELAJARAN DARING SISWA MTS KELAS VIII PADA MATERI STATISTIKA DI MASA PANDEMI COVID-19 - Pahmi Arip Maulana; Marchasan Lexbin Elvi Judah Riajanto (IKIP Siliwangi, 2021)
This study aims to analyze the online learning difficulties of class VIII MTs students on statistical material during the covid-19 pandemic. The method used in this study is a qualitative descriptive research method. Which aims to find out and analyze the difficulties of students in learning during the covid-19 pandemic on statistical material. The subjects used in this study were class VIII B students at MTs Al-Lutfhfah, totaling 25 students. The instruments used in this study consisted of an opinion scale for students regarding online learning constraints and statistical material test questions consisting of 6 test questions in the form of description questions. The results of the research obtained in this study are that there are still many students who have difficulty solving statistical problems, especially during the current pandemic, lack of understanding of material concepts and other non-technical obstacles such as the difficulty of accessing the internet for students who live in remote areas to make online learning. Encountered problems in its implementation.